Rancang Bangun Plugin WordPress Penghitung Kepadatan Kata Kunci - Adhi Kusnadi; Tirta Prawisuda (Universitas Multimedia Nusantara, 2016)
In optimizing a website, web owners are required to write articles that relate to the keywords and put into the website. Therefore is needed a keyword density plugin app to calculate keywords and suggest an article content writer to add or subtract keywords in the article. The keyword density counter is an app that counts keywords in an article. The results obtained from this application is the ratio of keywords to existing words of the pages of websites or articles. The benefits of using keyword density counters are content writers becoming aware that articles already have enough density, according Google's recommendation keywords density is 2-3% of article, then the article will give a signal to search engines. Results obtained is the same for validation plugin calculations after. Compared to other similar plugins. Keyword density counters have been created with 50.85% faster than other similar plugins. Index Terms—keyword, density, counter, article, plugin.